Formation of amorphous PbCrO4 nanoparticles depending on the quantitative control of interfacial water. Issue 11 (10th August 2021) - Wang, Chunli; Zhang, Zhihao; Fu, Xiaoheng; Zhang, Jing; Dhont, Jan K. G.
Abstract : By controlling water ratio in the micellar droplets, amorphous nanoparticles can be synthesized in the confined interfacial water, while nanocrystals are produced in the bulk water. Abstract : Interfacial water confined in the microemulsions shows behaviors different to normal bulk water and could affect the reactions involved at the interface. In this work, the content of interfacial and bulk water in the parental microemulsions for the reactions was first quantitatively determined by Fourier-transform infrared (FTIR) spectroscopy. The nucleation and growth of PbCrO4 nanoparticles in the microemulsions were studied on the basis of the FTIR results. By controlling the water ratio in micellar droplets, amorphous nanoparticles were obtained in the interfacial water, while nanocrystals were produced in the bulk water. The amorphous nanoparticles with defined shapes are quite stable in the microemulsion solution and show no transformation to crystallites for several days. This work offers a delicate way to control the metastable amorphous precursor for follow-up crystallization.